The influence of social and cultural practices on maternal mortality: a qualitative study from South Punjab, Pakistan - Sonia Omer; Rubeena Zakar; Muhammad Zakria Zakar; Florian Fischer (BMC, 2021)
Plain language summary Round the world, many women are dying because of complications during pregnancy or in childbirth. These deaths are more frequent in developing and underdeveloped countries. Some reasons for this are related to social and cultural factors, which form barriers to women using appropriate maternal healthcare. Therefore, this study aims to explore socio-cultural factors leading to a delay in seeking maternal healthcare in South Punjab, Pakistan. We interviewed a variety of people to get an overview of this topic: (1) 60 interviews were conducted with gynaecologists, (2) we performed four focus group discussions with eight to ten Lady Health Workers providing maternal healthcare, and (3) we talked with family members of mothers who had died. The study shows that delays in seeking care are related to poor socioeconomic status, limited knowledge about maternal care, and low incomes of rural people. The low status of women and male domination keeps women less empowered. In addition, early marriages and lack of family planning due to cultural values, religion and traditions stopped young girls from getting maternal healthcare. The number of new mothers who die is very worrying in Pakistan. One of the important tasks for reducing deaths among pregnant women is to address certain socio-cultural practices. It is very important to reduce poverty and improve decision-making power to make sure women can use their right to medical care.